Interlayer Mn-Mn exchange parameter MnPS3 from x-ray diffraction data - Yagotintsev, K.A.; Strzhemechny, M.A.; Prokhvatilov, A.I.; Stetsenko, Yu.E.; Vysochanskii, Yu.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The interlayer distance in MnPS3 was measured by x-ray diffraction as a function of the temperature in the vicinity of the Néel point of 78 K. A well detectable magnetic striction of about 0.0185% has been documented. Using the known values of the external-pressure driven compression and reasonable estimates of the range parameter of the separation dependence of the relevant Mn–Mn exchange parameter J′, we have estimated J′ to be about 1.0 K. From our analysis of the interlayer magnetic coupling, an inference is drawn that the Mn–Mn interlayer exchange can be strongly directional.